Targeting Myeloid-Derived Suppressor Cells Derived From Surgical Stress: The Key to Prevent Post-surgical Metastasis - Zhu, Sha; Zhao, Yunuo; Quan, Yuxin; Ma, Xuelei (Frontiers in Surgery, 2021)
Myeloid-derived suppressor cells (MDSCs) are known to play an essential part in tumor progression under chronic stress settings through their manipulation of adaptive and innate immune systems. Previous researches mainly focus on MDSC's role in the chronic tumor immune environment. In addition, surgery can also serve as a form of acute stress within the patient's internal environment. Nevertheless, the part that MDSCs play in post-surgical tumor development has not gained enough attention yet. Although surgery is known to be an effective definite treatment for most localized solid tumors, there are still plenty of cancer patients who experience recurrence or metastasis after radical resection of the primary tumor. It is believed that surgery has the paradoxical capability to enhance tumor growth. Many possible mechanisms exist for explaining post-surgical metastasis. We hypothesize that surgical resection of the primary tumor can also facilitate the expansion of MDSCs and their pro-tumor role since these surgery-induced MDSCs can prepare the pre-metastatic niche (the “soil”) and at the same time interact with circulating tumor cells (the “seeds”). This vicious, reciprocal mechanism is a crucial point in the emergence of post-surgical metastasis. According to our hypothesis, MDSCs can be the precise target to prevent cancer patients from post-surgical recurrence and metastasis during the perioperative phase to break the wretched cycle and provide better long-term survival for these patients. Future studies are needed to validate this hypothesis.